Cryolipolysis—An update. Issue 4 (23rd November 2020) - Pennycook, Keith; Lemchak, David; Julian, Carmen
Abstract: Background: Cryolipolysis is a noninvasive treatment for the reduction of localized adipose tissue. It is becoming an increasingly popular procedure since it received Food and Drug Administration approval in 2010. Localized collections of excess adipose tissue are cooled which results in selective apoptosis of adipocytes. Aims: Review of effectiveness and side effects of cryolipolysis treatments. Materials and Methods: Literature Review. Results: Studies have demonstrated the effectiveness of cryolipolysis for the treatment of several body regions. Cryolipolysis is contraindicated for patients with cold‐induced conditions and other cutaneous disorders. Most side effects are minor including erythema and local discomfort which typically resolve within a few weeks of the procedure. A rare complication of treatment is paradoxical adipose hyperplasia. Discussion: There are several other effective noninvasive modalities for reducing localized adipose tissue. Combining these treatments with cryolipolysis has been shown to be more effective. As technology improves, newer devices have been developed with improved applicators and beneficial results. Conclusion: Cosmetic procedures continue to increase in popularity and physicians should be familiar with cryolipolysis for the reduction of localized adipose tissue collections.